The Concept of Violence and its Expression in Criminal Law - Jurka, Raimundas; Zajanckauskiene, Jolanta; Marcinauskaite, Renata; Sukyte, Jolita (International Journal of Criminology and Sociology, 2022)
The very concepts of violence, studies of its forms from the criminal law viewpoint may be instrumental in dissociating criminalised violent actions from non-criminalised though having a legal significance or the actions falling outside the area of criminal regulation; furthermore, such studies can help identify the actions that in criminal law should be viewed as socially useful (for instance, the circumstances excluding criminal responsibility). It should be noted that the concept of violence and identification of its expression forms have not only a theoretical value, but also, as has been by this study proven, is applicable in legislation (for instance, for the purpose of criminalising different types of violence), as well as in case law (for instance, when identifying possible violence manifestation options). In the light of the above the present paper focuses on the definition of violence, the possible forms of its manifestation; the authors also looked into the specific forms the coercive criminal acts can acquire in the legislation.